A novel class of small molecule inhibitors with radioprotective properties - Marek, Jan; Tichy, Ales; Havelek, Radim; Seifrtova, Martina; Filipova, Alzbeta; Andrejsova, Lenka; Kucera, Tomas; Prchal, Lukas; Muckova, Lubica; Rezacova, Martina; Sinkorova, Zuzana; Pejchal, Jaroslav (European journal of medicinal chemistry, 2020)
The goal of this study was to develop novel radioprotective agents targeting the intrinsic apoptotic pathway and thus decreasing the radiation-induced damage. For that purpose, we designed, synthesized and analyzed ten new compounds based on the 1-(4-(2-hydroxyethyl)piperazin-1-yl)-3-phenoxypropan-2-ol leading structure. The cytotoxicity of the newly synthesized substances was tested in vitro on cell lines derived from different progenitor cells by WST-1 proliferation assay. MTT test was utilized to assess half-maximal inhibitory concentrations and maximum tolerated concentrations of novel compounds in A-549 cells. Screening for radioprotective properties was performed using flow-cytometry in MOLT-4 cells exposed to 60Co ionizing gamma radiation. Selected candidates underwent in vivo testing in C57Bl/6 J mice having a positive impact on their immunological status. In summary, we report here promising compounds with radioprotective effect in vivo.
Keywords: Synthesis; Propanols; Humans; simulace molekulového dockingu; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; In vitro; radioprotektivní látky; Dose-Response Relationship, Drug; Radiation-Protective Agents; 1-(2-hydroxyethyl)piperazine derivative; Molecular Docking Simulation; Radioprotection; lidé; Ionizing radiation; zvířata; proliferace buněk; myši; molekulární struktura; myši inbrední C57BL; Small Molecule Libraries; Mice; apoptóza; Molecular Structure; Cell Proliferation; Mice, Inbred C57BL; nádorové buněčné linie; propanoly; knihovny malých molekul; vztah mezi dávkou a účinkem léčiva; Animals; Cell Line, Tumor; Apoptosis